Rencana Aksi Berbasis Circular Economy untuk Mencapai SDG Target 11.6 “Pengelolaan Sampah Kota” (Studi Kasus: “Bank Sumber Daya Sampah” di Kota Cimahi) - Ratna Lindawati Lubis; Muhammad Luqman (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The issue of low-value plastic waste management has become a critical problem in Cimahi City, particularly due to the limited capacity of the existing landfill. This study aims to analyze the challenges and opportunities faced by Bank Sumber Daya Sampah (BSS) in implementing a circular economy model based on pyrolysis technology and to formulate a strategic action plan. This research employs a descriptive qualitative case study approach, collecting data through in-depth interviews, field observations, and documentation, and analyzing it using the four-dimension circular economy framework and SWOT analysis. The results indicate that BSS’s main obstacles include regulatory licensing burdens, the lack of long-term partnerships, limited funding, and low public participation. The discussion emphasizes the importance of policy advocacy, supply chain strengthening, capacity building for human resources, and financial sustainability to enhance operational resilience. The study concludes that an integrated strategic approach involving businesses, government, and the community is crucial to achieving SDG target 11.6 on effective urban waste management.